DISPOSITIVOS DGT MODIFICADOS COM MATERIAIS ALTERNATIVOS PARA USO NA ESPECIAÇÃO DE ELEMENTOS TRAÇO - Cristiano L. Chostak; Mônica S. de Campos; Simone B. da Silva; Gilberto Abate; Marco T. Grassi (Química Nova, 2015)
The use of MT-K10 Montmorillonite immobilized onto agarose was investigated in this work as an alternative binding phase in Diffusive Gradient in Thin Film (DGT) devices for the determination of metallic labile species. In addition, agarose itself was also used as the diffusive phase. The percentage of sorption of Zn2+, Cu2+, Cr3+, Mn2+, Cd2+, Pb2+, and Ni2+ onto the binding phase was higher than 80% and the desorption process for all elements was also greater than 75%. Elution factors were determined experimentally, ranging from 0.74 for Zn2+ and 0.90 for Cr3+ and Pb2+. The accumulation of all species was linear with time, in agreement with the Fick's 1st law of diffusion. The deployment of the alternative devices in natural waters was compared to commercial devices. Labile concentrations determined by the alternative devices were slightly superior compared to results obtained with the deployment of original DGT devices due to the less restrictive pores of agarose.